Final answer:
To solve for c in the equation a(c – b) = d, distribute a, add ab to both sides, and then divide by a to get c = (d + ab) / a.
Step-by-step explanation:
To solve for the variable c in the equation a(c – b) = d, follow these steps:
- Distribute the a across the parentheses by multiplying it with both c and –b, which gives us ac - ab = d.
- Add ab to both sides of the equation to isolate the term with c on one side, resulting in ac = d + ab.
- Finally, to solve for c, divide both sides of the equation by a, giving us c = (d + ab) / a.
By following these steps, you'll find the value of c in terms of a, b, and d.